Dimension groups associated to β-expansions - Bates, Teresa; Carlsen, Toke Meier; Eilers, Søren (Mathematica Scandinavica, 2007)
Completing work by Shultz on one hand and by Katayama, Matsumoto, and Watatani on the other, we prove that a priori different dimension groups associated to β-expansions in fact coincide.